Early attempts to establish Korean diplomatic representation in Europe in the late 19th century - Daria E. Grishina (RUDN Journal of World History)
The opening of Korea (Chosŏn) for modern diplomacy in the late XIX century not only had a signifi impact on the geopolitical balance of power in the Northeast Asian region, but also largely determined the future of the Korean Peninsula. Chosŏn’s immediate neighbors, China, Japan, and the Russian Empire, played a particularly important role in the regional rivalry surrounding the Korean peninsula in the late XIX and early XX centuries. First two powers had a long history of traditional diplomatic communications with Chosŏn and the states that preceded it. However, the Russian Empire, which expanded its territory in the Far East in the mid-19th century, was a new force in the region. Its diplomatic line followed Western, rather than Sinocentric, standards. It was precisely this unique position of the Russian Empire that determined its key role for Korea in establishing its diplomatic representation in Europe. This study describes several attempts by the Chosŏn government to establish its permanent diplomatic representation in Europe (headquartered in St. Petersburg) in the mid-1880s to late 1890s. These episodes in the history of Russian-Korean relations still remain poorly understood. The author focuses on the balance of power surrounding the Korean Peninsula during these events and analyzes the reasons for the failure of mentioned Korean government’s initiatives in the context of the geopolitical situation of that time. Despite the negative outcome, these early attempts to establish a Korean diplomatic representation in Europe (and Russia) had a signifi impact not only on the dynamics of domestic political processes in Chosŏn, but also on the balance of power surrounding it at the end of the XIX century.